Aplicações comerciais para dispositivos móveis usando QR-Code - Alonso, Alailson Bolzon (2013)
Given the technological advancement in the mobile phones field, with the emergence of the smartphones and the Internet becoming more accessible, it has become practicable to implement a project that linking a web application to a mobile application. The QR-Code (Quick Response Code) tool is widely used in Japan, United States and South Korea. In those countries the QR-Code is used for several purposes such as product purchasing and inventory control. In Brazil, it is used for advertising performing redirection to virtual addresses for promotion of products. In this paper will be presented a system of interactive movie theater, using QRCode to buy tickets and even present it as a voucher at the entrance of the movie theater.